2022
DOI: 10.1002/ijc.34154
|View full text |Cite|
|
Sign up to set email alerts
|

Racial and ethnic disparities in nasopharyngeal cancer with an emphasis among Asian Americans

Abstract: Despite the overall decreasing incidence, nasopharyngeal cancer (NPC) continues to cause a significant health burden among Asian Americans (AAs), who are a fastgrowing but understudied heterogeneous racial group in the United States. We aimed to examine the racial/ethnic disparities in NPC incidence, treatment, and mortality with a specific focus on AA subgroups. NPC patients aged ≥15 years were obtained from the Surveillance, Epidemiology, and End Results (SEER) 18 . AAs were divided into Chinese, Filipino, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Married patients may receive more encouragement from their families and are more likely to engage in healthy behaviors and actively seek treatment. Some studies have shown that racial differences have a signi cant impact on the prognosis of NPSCC [19] [20] , which aligns with our ndings. This may be attributed to variations in diet and health behaviors, such as the consumption of salted or pickled foods and tobacco use [21,22,23] .…”
Section: Discussionsupporting
confidence: 92%
“…Married patients may receive more encouragement from their families and are more likely to engage in healthy behaviors and actively seek treatment. Some studies have shown that racial differences have a signi cant impact on the prognosis of NPSCC [19] [20] , which aligns with our ndings. This may be attributed to variations in diet and health behaviors, such as the consumption of salted or pickled foods and tobacco use [21,22,23] .…”
Section: Discussionsupporting
confidence: 92%
“…For oral cavity cancer, there is a higher incidence in Native American and Asian American/Pacific Islander populations [ 29 ]. Laotian individuals have 18.04 times higher risk of developing this nasopharyngeal carcinoma than non-Hispanic White individuals [ 34 ]. Compared to White patients, American Indian patients had a greater risk of alcohol abuse (68% vs 42%), current smoking (67% vs 49%), living more than 1 h away from a cancer center (81% vs 30%), and delayed presentation with stages III and IV HNC (74% vs 55%) [ 35 ].…”
Section: Healthcare Disparities Across Otolaryngology Subspecialitiesmentioning
confidence: 99%
“…By integrating variables identified to have a significant impact on outcome, nomograms are excellent visualization tools for the estimation of survival rates, but also identify the critical parameters responsible for survival (15). Reported studies examining into some specific subgroups of NPC, including some tumor stage (16)(17)(18)(19)(20)(21)(22), patient age (20,(23)(24)(25)(26), histologic type (27)(28)(29) and even race (30)(31)(32), in a wide scope based on the Surveillance, Epidemiology, and End Results (SEER) data, have shown the potential and ability to provide a better reference for clinical decisions (16,21,23). However, few studies have specifically focused on LA-NPC patients as a group using the SEER data.…”
Section: Introductionmentioning
confidence: 99%